Advanced thermodynamics for engineers - Wark, Kenneth (McGraw-Hill, 1995)
This book is composed of thirteen chapters. The first two chapters are used to review and extend basic first-and second-law concepts. The third and fourth chapters discuss the theory and application of availability (or exergy) concepts to nonreactiveprocesses and cycles. The fifth and sixth present the theory and experimental correlations for the important properties of simple compressible substances. The seventh is a short discourse on the third law, modeling of specific-heat data, and experimental work in this area. The eighth covers the general theory of multicomponent, single phase systems, including the concepts of a partial molal property and the chemical potential. The ninth extends this discussion to multiphase, multicomponent systems. The tenth presents general coverage of the first-and second-law applications to reacting systems. The eleventh introduces chemical availability and the environmental dealstate for reactive systems. The twelfth deals with the chemical availability of fuels the concepts of the standard chemical availability. The final chapter provides insight into the microscopic or molecular origins of the entropy function, heat and work, and the second law of thermodynamics